Comparison of cone beam computed tomography and plane radiographs of radial fractures as a basis for radiographical measurements - Kristian Bry; Mika Kortesniemi; Mika Koivikko; Liisa Kerttula (BMC Medical Imaging, 2023)
Abstract Background The purpose of this study was to determine whether radiological measurements of radial fracture position made in cone beam computed tomography (CBCT) projection images are comparable to those made on traditional radiographs and could potentially substitute them. Methods Sixteen patients with fractures of the distal radius referred for radiographs were recruited for an additional CBCT scan which was performed immediately afterwards. Projection images and volumetric data were saved from the CBCT scans. Measurements of ulnar variance, radial inclination and volar tilt were made from all three sets of images. Results Agreement of projection image based measurements with radiographs was nearly as good as as the agreement of cross sectional image measurements with radiographs. The average difference between the results for projection images and radiographs were -1.2 mm (SD 1.9 mm), for radial inclination 0.7° (SD 2.9°) and for volar tilt 1.9° (SD 5.6°). Conclusion Differences between radiological measurements between the modalities studied are small and projection images could be used for the assessment of distal radial fractures.